Development of AI-Based Hypercontent E-LKPD for IPAS Learning in Grade V Elementary School - Sri Murwani; Syarifuddin; Riswan Jaenudin (Postgraduate, University of Mataram, 2025)
Learning that still relies on conventional methods, such as lectures and textbooks, often fails to facilitate understanding of complex concepts, especially in subjects like Natural and Social Sciences (IPAS), which require in-depth and contextual understanding. Learner-centered education should be enhanced through innovative learning media, including the use of AI-based Hypercontent E-Worksheets (E-LKPD) to assess learning effectiveness. This study aims to develop a valid, practical, and effective AI-based Hypercontent E-LKPD for IPAS (Social and Natural Sciences) learning in Grade V of elementary school. The research was conducted in Class V of SDN 10 Sekayu with 50 student participants. The study followed a Research and Development (R&D) approach using the Rowntree development model and Tessmer’s formative evaluation. Data were collected through interviews, questionnaires, expert reviews, one-to-one and small group evaluations, and pretest-posttest. The validity score of the developed E-LKPD was 4.62 (very good). Practicality scores were 4.6 (one-to-one) and 4.42 (small group), both considered very practical. Effectiveness was measured through learning outcomes, showing a pretest score of 42.50%, a posttest average of 84.75%, and an N-Gain of 0.72 (high category). These results indicate that the developed AI-based Hypercontent E-LKPD is valid, practical, effective, and highly suitable for use in IPAS learning for Grade V elementary students.